BEST RECRUITMENT AND SELECTION PRACTICES BASED ON HRM LITERATURE REVIEW - Loso Judijanto; Hadenan Towpek; Mohd Syahrin (CV. Adiba Aisha Amira, 2025)
This research explores recruitment and selection best practices based on a literature review in the field of Human Resource Management (HRM). The main objective of this research is to identify effective approaches in securing the right talent and improving the efficiency of the recruitment process. The method used involved analysing various literatures. The results of the study show that the development of clear and detailed job descriptions is a crucial first step in attracting candidates that match the needs of the organisation. Furthermore, the use of technology such as application tracking systems (ATS) and social media is proven to increase the reach and efficiency of the recruitment process. Assessments through competency-based interview methods, psychometric tests, and practical skills assessments provide comprehensive information on candidates' abilities and cultural fit. Multi-stakeholder participation in the evaluation process helps ensure objectivity and fairness in selection. Implementation of these practices can reduce turnover costs, improve recruitment quality, and support long- term growth through competent and motivated human resources.